Poly(butylene trisulfide)/SiO2 nanocomposites: cure and effect of SiO2 content on mechanical and thermophysical properties. (4th July 2022) - Sheydaei, Milad; Edraki, Milad; Mousazadeh Moghaddampour, Issa; Alinia-Ahandani, Ebrahim
Abstract : In this work, poly(butylene trisulfide) (PBTRS) was synthesized using 1, 4-dichlorobutane (DCB) organic monomer and sodium trisulfide (Na2 S3 ) aqueous monomer. Then, the PBTRS with silicon dioxide (SiO2 ) nanoparticles, sulfur, zinc oxide (ZnO), stearic acid, and N -cyclohexyl-2-benzothiazole sulfenamide (CBS) were compounded using a two-roll mill and cured by a rheometer at 85°C. The PBTRS characteristics were investigated by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), proton nuclear magnetic resonance ( 1 H NMR), and differential scanning calorimetry (DSC). Also, cured samples were investigated by scanning electron microscopy (SEM), FT-IR spectroscopy, XRD, and DSC. Moreover, the mechanical properties and hardness of the samples were investigated by tensile test and Shore A. The results showed that after the curing process, the structure is completely amorphous and no melting temperature ( Tm ) has been observed and by increasing SiO2 in matrix, the glass transition temperature ( Tg ) occurs at higher temperatures. Moreover, by an increase of SiO2, hardness, and elastic modulus, as well as strength, were increasing. Furthermore, cured samples were insoluble in solvents, but the PBTRS was slightly dissolved in dimethyl sulfoxide (DMSO). GRAPHICAL ABSTRACT: UF0001